دراسة التركيب الكيميائي لقشور بعض أنواع الروبيان واستخلاص وتشخيص الكاروتينويدات الفعالة حيوياٌ: هيفاء علي عواد مازن جميل هندي - عواد, هيفاء علي; هندي, مازن جميل (Journal of Kerbala for Agricultural Sciences, 2017)
تمت دراسة التركيب الكيميائي لقشور الروبيان الرطبة والمجففة للأنواع Penaeussemisulcat و Penaeus japonicas و Exopalamon styliferus , الذي تم شرائه من أسواق بغداد , حيث بلغت نسب الرطوبة والرماد والدهن والبروتين 31 , 2.06 , 27 , 14.5 )% ) للعينات المجففة وبلغت 16 , 1 , 11 , 72% للعينات الرطبة على التوالي . استخدمت طرائق كيميائية مختلفة لأستخلاص الكاروتينويدات الخام من قشور الروبيان المجففة والرطبة . شملت الطريقة الأولى طريقة الأستخلاص الساخن بأستخدام مزيج المذيبات الآيثانول والبتروليوم أيثر ( 1 : 1 ح :ح ) وبأستعمال جهاز السوكسليت في درجة حرارة 50مْ وشملت الطريقة الثانية والثالثة النقيع الحامضي والقاعدي لمدة 48 ساعةبأستخدام حامض الهايدروكلوريك HCL1N )) والقاعدة هيدروكسيد الصوديوم 1N )) على التوالي . شملت الطريقة الرابعة الأستخلاص بزيت زهرة الشمس (1 : 1) . شملت طريقة الأستخلاص البارد بأستعمال ثلاث توليفات مختلفة من المذيبات العضوية تمثلت بالمعاملات T5 و T6 و T7 أذ تضمنت المعاملة T5 ألأستخلاص بواسطة الأيثانول %100 وتضمنت المعاملة T6 ألاستخلاص بمزيج المذيبات هكسان وأسيتون ( 1: 1,ح : ح ) أما المعاملة T7 تضمنت أستخدام مزيج المذيبات الهكسان والأسيتون 1 : 2 ) , ح : ح ). تم الحصول على أعلى حاصل للكاروتينويدات عليه باستخدام توليفة المذيبات العضوية المتكونة من هكسان وأسيتون 1:1 ( حجم / حجم ) إذ بلغت 0.08 ملغم/غم وبنسبة أستخلاص 80% للعينات المجففة . تم تنقية وتجزئة المستخلصات الكاروتينويدية بتقنية العمود السائل باستعمال عمود هلام السليكا 0.963 – 0.200)) والمذيبات العضوية الهكسان والاسيتون وثنائي أثيل ايثر وشخصت مكونات المستخلص بتقنية كروموتوغرافي العمود عالي الأداءHPLC)) بوجود المركبات القياسية وظهرت المركبات الكيميائية الآتية: Β- carotene , ِAstaxanthin , Leutin , Violastaxanthin وحامض السالسيلك بتركيز42.50 , 19.50 , 32.50 , 41.25, 46.75) ) ملغم/ مل على التوالي . شخصت مكونات المستخلص بتقنية الأشعة تحت الحمراء IR)) وفي جهاز المطياف الضوئي نانوميتر بوجود المركبات القياسية للتأكد من نوعيتها . Study Of The Chemical Composition Of Some Shrimp's Shell And Extraction , Identification Of Bioactive Carotenoids H.A.Awad* M.J.Hindi University of kerbala / College of Agriculture |* University of Baghdad /College of Agriculture/ Dep. of Food Science Abstract This investigation was carried out to evaluate the activity of Carotenoids extracted from shrimp shell related to Penaussemisculcats, Penausjaponicas and Exopalamon styliferus that obtained from retail out in Baghdad – Iraq. The chemical composition of shrimp shell was 14.5 , 27 , 2.06 and 31% for moisture , ash , fat and protein respectively for dried sample , while the alternative values for wet samples were 72 , 11, 1, 16% respectively. Different methods were employed for Carotenoids extraction from dried shrimp shell that included hot extraction by Soxhelet with petroleum ether and ethanol ( 1:1) volume : volume at 50C°. The seconed method (T2) included extraction by acidic extraction with HCL (1N) ,alkaline extraction (T3) by NaOH (1N ), Sunflower oil extraction (T4).Cold extraction with different organic solution by three mixtures combinations that included absolute ethanol 100% (T5) , Hexane : Acetone ( 1:1, V:V) (T6) and Hexane : Acetone ( 2: 1, V: V ) (T7) . The treatment (6) of Hexane : Acetone ( 1:1, V:V) was adopted as highest carotenoids yield was obtained and valued 0.08 µg/g with 80% extraction rate as compared to the aforementioned methods. The Carotenoides extract was fractionated on Silca gel liquid Column Chromatography (LPLC) with Hexane , Aceton and diethyl ether was used for elution . The fractions of crude extracts were then identified by High performance Liquid Chromatography ( HPLC )and the chemical compounds were β- Carotene , astaxanthin , Leutin , Violastaxanthin and Salicylic acid was existed at rates of 46.75 , 41.25, 32.50 , 19.50 and 42.5 µg/ml respectively . The crude extraxct components were further identified by both IR and Spectroscopy and compared with standard compounds .